The Effect of Audio Visual Media and Learning Style On Students' Learning Achievement in Class IV Thematic Learning at Fourth Islamic Elementary School Nganjuk - A. Jauhar Fuad; Erna Sa’bandiyah (eL Bidayah: Journal of Islamic Elementary Education, 2023)
This study aims to determine (1) the effect of the application of audio-visual media on student achievement in thematic learning. (2) The influence of learning styles on student achievement in thematic learning. (3) The effect of the application of audio-visual media and learning styles on student achievement in thematic learning. This research is an experimental research using the initial test (pre-test) and the final test (post-test). The research was conducted at MIN 4 Nganjuk. The population of this study were all students of MIN 4 Nganjuk amounting to 616 students. The sample of this study was 63 students who were taken by using cluster random sampling technique. The data analysis technique used two-way anova. The results showed (1) There was an effect of the application of audio media on the learning achievement of students in thematic learning. (2) There is an influence of learning style on student achievement in thematic learning. (3) There is an effect of the application of audio media and learning styles on student achievement in thematic learning [Penelitian ini bertujuan untuk mengatahui (1) Pengaruh dari penerapan media audio visual terhadap prestasi belajar peserta didik pada pembelajaran tematik. (2) Pengaruh dari gaya belajar terhadap prestasi belajar peserta didik pada pembelajaran tematik. (3) Pengaruh media audio visual dan gaya belajar terhadap prestasi belajar peserta didik pada pembelajaran tematik. Penelitian ini merupakan penelitian eksperimen dengan menggunakan tes awal (pre-test) dan tes akhir (post-test). Penelitian dilakukan di MIN 4 Nganjuk. Populasi penelitian ini adalah seluruh peserta didik MIN 4 Nganjuk yang berjumlah 616 siswa. sampel penelitian ini sebanyak 63 siswa yang diambil dengan teknik cluster random sampling. Teknik analisis data menggunakan anova dua jalur. Hasil penelitian menunjukkan: (1) Terdapat pengaruh penerapan media audio terhadap prestasi belajar peserta didik pada pembelajaran tematik. (2) Terdapat pengaruh gaya belajar terhadap prestasi belajar peserta didik pada pembelajaran tematik. (3) Terdapat pengaruh penerapan media audio dan gaya belajar terhadap prestasi belajar peserta didik pada pembelajaran tematik]